Management of lateral incisor with palatal radicular groove - Hans Manoj; Srinivas Ramachandra; Shetty Shashit (Wolters Kluwer Medknow Publications, 2010)
Palatal radicular grooves are developmental anomalies of maxillary incisors, which contribute to localized periodontitis resulting in loss of anterior teeth. Palatal radicular grooves, when present, act as a site for plaque accumulation and periodontal infection. They are easily overlooked as etiologic factors, as these grooves are covered by periodontal tissues. The clinician has to be alert and check for variations in the anatomy of the tooth as a cause of pulp necrosis in the anterior segment of the tooth, when other causes are ruled out. Recognition of palatal radicular grooves is critical, especially because of its diagnostic complexity and the problems that may arise if it is not properly interpreted and treated. This case report describes the diagnosis and management of a maxillary lateral incisor with necrotic pulp and localized periodontal destruction, associated with a palatal radicular groove.